2017
DOI: 10.1530/joe-16-0452
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aldosterone secretion by mineralocorticoid receptor–mediated signaling

Abstract: We posit the existence of a paracrine/autocrine negative feedback loop, mediated by the mineralocorticoid receptor (MR), regulating aldosterone secretion. To assess this hypothesis we asked whether altering MR activity in zona glomerulosa (ZG) cells affects aldosterone production. To this end, we studied ex vivo ZG cells isolated from male Wistar rats fed chow containing either high (1.6% Na+ [HS]) or low (0.03% Na+ [LS]) amount of sodium. Western blot analyses demonstrated that MR was present in both the ZG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
1
21
0
3
Order By: Relevance
“…Indeed, a number of in vitro and in vivo studies have shown that prior exposure of the adrenal gland to glucocorticoids results in a decreased response to ACTH. For example, CORT synthesis in response to ACTH is reduced in cultured adrenal cells treated with high levels of CORT or DEX (Carsia & Malamed, 1979 ; Chong et al., 2017 ; Peron, 1960 ). These findings are consistent with studies showing lower responses to ACTH in adrenals collected from hypophysectomized rats treated with CORT, when compared with adrenals from untreated rats (Langecker & Lurie, 1957 ).…”
Section: Regulation Of Corticosterone Synthesismentioning
confidence: 99%
“…Indeed, a number of in vitro and in vivo studies have shown that prior exposure of the adrenal gland to glucocorticoids results in a decreased response to ACTH. For example, CORT synthesis in response to ACTH is reduced in cultured adrenal cells treated with high levels of CORT or DEX (Carsia & Malamed, 1979 ; Chong et al., 2017 ; Peron, 1960 ). These findings are consistent with studies showing lower responses to ACTH in adrenals collected from hypophysectomized rats treated with CORT, when compared with adrenals from untreated rats (Langecker & Lurie, 1957 ).…”
Section: Regulation Of Corticosterone Synthesismentioning
confidence: 99%
“…Synthesis and release of Aldo, by the adrenal cortex, are promoted by the RAS and potassium ions (K + ) that are considered main triggering factors, as well as by minor stimulators like adrenocorticotropin (ACTH) and vasopressin (VP) [ 11 15 ]. Conversely, other molecules such as dopamine and atrial natriuretic peptide (ANP) exert an inhibitory effect on Aldo production/release [ 14 , 16 ].…”
Section: Aldosterone: From Biosynthesis To Releasementioning
confidence: 99%
“…The biological processes underlying this self-inhibition are not known, but the glucocorticoid receptor (GR) is expressed in the adrenal cortex (15,18). Furthermore, the synthetic glucocorticoid dexamethasone-a specific GR agonist-has been shown to inhibit ACTH-induced corticosterone secretion from rat adrenocortical cells (19) as well as the transcription of steroidogenic genes through a mechanism that involves GRand SF-1-mediated induction of DAX-1 expression (20).…”
mentioning
confidence: 99%